Sonatas and other piano works, ed. by Bülow, vol. 4 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Bülow, Hans von, 1830-1894 (editor):::Contributor:::::::::::: (Germany; J. G. Cotta; Stuttgart, 2024)
Volume 4 of the Sonaten und andere Werke für das Pianoforte von Ludwig van Beethoven, from the Instruktive Ausgabe klassischer Klavierwerke, Abt. 3, containing the Piano Sonatas opp. 53; 54, 57, 78, 79, 81a, and 90; the 6 Variationen op. 76; Fantasie, op. 77; and the Polonaise, op. 89.